Navigating School-Based Special Education Services: A Self-Paced Virtual Learning Module - Demvihin Ihyembe; Kelli Stager; Alexis Deavenport-Saman; Jeffrey Yang; Karen Kay Imagawa; Douglas L. Vanderbilt (Association of American Medical Colleges, 2021)
Introduction Children with disabilities are particularly vulnerable to school failure, as they are more likely than their peers to experience school dropout and academic struggles. Early identification of learning difficulties and access to special education services are critical to the success of children with disabilities. However, few pediatricians feel competent in screening for risks of school failure and/or assisting families with navigating the special education system. Due to restricted duty hours and limited scheduled didactic time during residency, flexible training options are needed to fill this educational gap and address this systems-based practice competency. Methods We developed a 30-minute self-paced virtual learning module aimed at educating pediatric residents on strategies for navigating the special education system. The module used a knowledge, attitudes, and self-efficacy framework, as well as case examples and pictorial relationships to illustrate concepts. Wilcoxon signed rank tests were conducted to assess changes in total knowledge, attitude, and self-efficacy scores. Results After completion of the module, residents' self-efficacy total scores significantly increased (r = .88, p = .001), suggesting that they were more confident in their ability to identify, recognize, and advocate for special education services. Discussion This virtual learning module successfully increased resident self-efficacy in screening for school failure and navigating the special education system. This highly feasible, self-paced training module can be modified to fit demanding resident schedules and serves as a potential tool to teach trainees and other pediatric providers about the special education system.